2013
DOI: 10.1111/jocn.12440
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a self‐management programme for people with diabetes, after a special training programme for healthcare workers in Taiwan: a quasi‐experimental design

Abstract: The diabetes care professionals are provided the self-management programme to strengthen the awareness and importance of self-management in diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 23 publications
(34 reference statements)
2
16
0
2
Order By: Relevance
“…This study demonstrated that the HETF improved the self‐efficacy of RA patients, even when considering the time cumulative effect and the patients who were lost to follow‐up. Our results were similar to the results of Koberich and Wu (Koberich, Lohrmann, Mittag, & Dassen, ; Wu, Liang, Lee, Yu, & Kao, ). Health education has been widely applied to the learning of knowledge and skills about self‐management.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated that the HETF improved the self‐efficacy of RA patients, even when considering the time cumulative effect and the patients who were lost to follow‐up. Our results were similar to the results of Koberich and Wu (Koberich, Lohrmann, Mittag, & Dassen, ; Wu, Liang, Lee, Yu, & Kao, ). Health education has been widely applied to the learning of knowledge and skills about self‐management.…”
Section: Discussionsupporting
confidence: 92%
“…None of the included studies scored the maximum quality score of 9 points. Among the 14 reviewed studies, one (Trief et al, ) had a methodological quality score of 8, one (Wattana, Srisuphan, Pothiban, & Upchurch, ) had a score of 6, four (Atak, ; Hawkins, ; Moriyama et al, ; Wu et al, ) had 5, two (Siminerio, Ruppert, Emerson, Solano, & Piatt, ; Wu, Liang, Lee, Yu, & Kao, ) had 2, and the remaining 6 studies (Clarke, ; Johnson et al, ; Karakurt & Kas¸ıkçı, ; Landim, Zanetti, Santos, Andrade, & Teixeira, ; McEwen et al, ; Ve'g, Rosenqvist, & Sarkadi, ) had a quality score of 1 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of interventions used in improving self‐management skills among people with type 2 diabetes. Diabetes self‐management programmes of reviewed studies had patient education delivered in individual and group sessions (Clarke, ; Karakurt & Kas¸ıkçı, ; Landim et al, ; McEwen et al, ; Siminerio et al, ; Wattana et al, ) on diabetes self‐care (Wu et al, ), pathology, healthy lifestyle habits, medication use and adherence (Johnson et al, ), self‐management behaviour, diet, exercise, complications of weight control, and foot care (Atak, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines to control blood glucose levels include self-care activities such as on-going blood glucose monitoring, medication administration, nutritional therapy, and increasing activity levels [2]. According to illness management frameworks, self-care and treatment choices are heavily reliant on an individual's decision-making that involves personal self-efficacy, the resources to manage diabetes, balancing social responsibilities, and desiring normalcy [3][4][5]. While the nature of DM and management generally require personal motivation, self-knowledge, goals and decision-making, which are strong, individualistic or independent ideals originated from a biomedical perspective [6,7], the personal management models may not fully explain the experience of immigrants to the United States [8] or take into consideration of the traditional KAI culture and efforts to maintain family and community cohesion [9].…”
Section: Introductionmentioning
confidence: 99%